2022
DOI: 10.7573/dic.2021-9-4
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran in patients with atrial fibrillation after COVID-19 hospitalization: an update of the ANIBAL* protocol

Abstract: COVID-19 increases the risk of atrial fibrillation (AF) and thrombotic complications, particularly in severe cases, leading to higher mortality rates. Anticoagulation is the cornerstone to reduce thromboembolic risk in patients with AF. Considering the risk of hepatotoxicity in patients with severe COVID-19 as well as the risk of drug–drug interactions, drug-induced hepatotoxicity and bleeding, the ANIBAL protocol was developed to facilitate the anticoagulation approach at discharge after COVID-19 hospitalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…6 In this context, these oral anticoagulants, with a lower risk of hepatotoxicity could provide an added benefit in this clinical setting. 33 This study has some limitations that should be commented. This registry had a retrospective design.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…6 In this context, these oral anticoagulants, with a lower risk of hepatotoxicity could provide an added benefit in this clinical setting. 33 This study has some limitations that should be commented. This registry had a retrospective design.…”
Section: Discussionmentioning
confidence: 88%
“…Of note, in our study, no differences in outcomes were observed in patients taking LMWH versus other anticoagulants. Although during the first wave, experts considered that oral anticoagulant treatment should be switched to LMWH mainly due to the risk of drug-drug interactions, leading to important changes in the efficacy or safety of oral anticoagulants, 31 , 32 the fact is that this has not been confirmed in further studies, 33 , 34 and except in cases in which oral ingestion is not possible (ie mechanical ventilation), the use of direct oral anticoagulants during hospitalization should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Dabigatran is associated with a lower risk of both hepatotoxicity and interaction with COVID-19 treatments that are metabolised by cytochrome P450 ( 55 ). In fact, dabigatran was initially suggested to be the first choice for oral anticoagulation in hospitalised patients with AF and COVID-19 ( 56 , 57 ) due to the low risk of interactions with antiviral therapies, the low risk of hepatotoxicity, the lack of metabolism by cytochrome P450, and the availability of specific reversal agent. With the widespread use of dexamethasone for COVID-19, dabigatran or edoxaban at discharge have been recommended because of the low risk of drug-drug interactions ( 57 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, dabigatran was initially suggested to be the first choice for oral anticoagulation in hospitalised patients with AF and COVID-19 ( 56 , 57 ) due to the low risk of interactions with antiviral therapies, the low risk of hepatotoxicity, the lack of metabolism by cytochrome P450, and the availability of specific reversal agent. With the widespread use of dexamethasone for COVID-19, dabigatran or edoxaban at discharge have been recommended because of the low risk of drug-drug interactions ( 57 , 58 ). The use of dexamethasone concomitantly with apixaban or rivaroxaban in hospitalised COVID-19 patients with coagulopathy should be avoided because of the interactions ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…RDV is usually prescribed with APX for severe and hospitalized cases of COVID-19 aiming to reduce the risk of severe thromboembolic complications and death [32] , [33] . To date, no analytical methods have been developed that allow determination of the drugs under study in spiked human plasma.…”
Section: Introductionmentioning
confidence: 99%